(untitled) (Research, Society and Development, 2022)
Introduction: Musictherapy encompasses numerous treatments that help in different behaviors that can relate to physical therapy, showing a good development in different neurofunctional pathologies. Objectives: To describe the importance of music therapy with physiotherapy in functional rehabilitation. Methodology: A bibliographic, descriptive and exploratory review study with published articles and intellectual productions, covering the period from 2008 to 2022. Results: The role of music therapy associated with physical therapy is fundamental in the rehabilitation of different pathologies, enabling neuroplasticity associated with gains functional, favoring the performance of the physical therapist. Conclusion: The performance of physiotherapy associated with music therapy helps and stimulates the Central Nervous System (CNS), favoring the individual’s return to activities of daily living, recovering what he had lost and. enhancing the patient’s functions.